United States : Financial Sector Assessment Program-Systemic Risk Oversight and Management-Technical Notes. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note discusses the findings and recommendations made in the Financial Sector Assessment Program for the United States in the areas of systemic risk oversight and management. Significant steps have been taken by the U.S. authorities to reduce risks in a number of areas, but progress is most advanced in the area of banking sector resilience, and less so in other areas which play a major role in the financial system. Further actions are needed to address data gaps, resolve remaining impediments to data sharing, support coordination and consultation on prudential standards and regulations, enhance risk monitoring frameworks, and provide additional clarity on the nature and scale of identified emerging systemic threats.